Fundamentals of ductile cast iron scuffing at the boundary lubrication regime. (October 2015) - Wojciechowski, Ł.; Eymard, S.; Ignaszak, Z.; Mathia, T.G.
Abstract: The friction regime of partially lubricated and highly loaded contact when the oil does not entirely separate the rubbing surfaces and its thickness is comparable to the roughness of the surfaces poses, in some cases, risk of scuffing and catastrophic wear. The present study, on life prediction of tribological systems from ductile cast iron, steel and brass, is shown by an analysis of the fundamental mechanisms of scuffing. Ductile cast iron according to DIN EN 1563 with nodular graphite standard EN ISO 945 is submitted to systematic tribological tests of scuffing and analysed in the context of quasi-conventional tribometry lubricated with reference and reclaimed naphthenic oils. The 3D morphologies of the rubbing surfaces are characterised and the fundamental conditions of the scuffing process are investigated. The results are elucidated in order to propose a phenomenological description of the analysed wear process and its invariants. Therefore, the role of solid materials as well as the nature of lubricants is both taken into consideration. Highlights: We proposed the scuffing energy as a parameter specifying an activation of scuffing. We found out that appropriately composed DCI exhibits a good scuffing resistance. We found that reclaimed naphthenic oils can offer competitive scuffing performance. We recognised a specific decrease of temperature and COF in DCI scuffing activation. We confirmed a topography distribution as a factor supported a scuffing resistance.